Dinamika Populasi Nephotettix virescens pada Dua Pola Tanam Padi Sawah - I Nyoman Widiarta; Dede Kusdiaman; Andi Hasanuddin (Jurnal Perlindungan Tanaman Indonesia, 1999)
Planting pattern of irrigated rice in Indonesia can be categorized generally into consecutive rice-rice-rice and rice-rice-fallow/secondary crop patterns. A study was conducted in farmer’s fields in two planting patterns in 1997 and 1998 to elucidate population dynamics of green leafhopper, vector of tungro disease and factors affecting their dynamics. A susceptible rice variety to green leafhopper was planted three times in one season with monthly interval between planting time. The rice was planted following farmer usual practices except no insecticide was applied. The population of green leafhopper and their natural enemies was surveyed by sweeping net. The egg predator and parasitoid were observed by dissecting the rice stems and incubating the discovered eggs. Life table of the first generation was constructed. The key-factor analysis was conducted to identify the key-mortality factor by regression methods. Numerical response of natural enemies was also analyzed to know the relationship of key-mortality to predator. Population density of green leafhopper increased mainly during early stage of rice growth in the rice-rice-rice planting pattern, but in the rice-rice-fallow/secondary crop planting patterns showed almost no population increase at all. The nymph mortality including adult disappearance before maturation was the key mortality for the population in both planting patterns. However, there were different in population process between population in different planting patterns. In contrast to the rice-rice-secondary crop, there were no numerical response between nymphal mortality and predator density in the rice-rice-rice planting pattern. In the rice-rice-rice planting pattern adults dispersal played important role. Therefore to control tungro, reducing feeding and inoculation ability of green leafhopper was considered important. In the rice-rice-secondary crop, natural enemies conservation especially the predator was considered important.